Semiotics Analysis Moral Message Of Film “Hichki” - Niswah, Nur Luthfiatun (Pena Cendekia Insani, 2022)
This research is entitled Semiotic Analysis of Hichki's Film Moral Message. This study tells about a woman who has Tourette's syndrome and wants to become a teacher, but is difficult to accept because of a rare disease she suffers from. For five years trying to get into various schools finally paid off, he was accepted at one of the schools where he studied after being rejected five times at that school. However, he was given students who came from underprivileged families, which made him a lot of challenges to stay afloat in the face of the behavior of 14 students in his class. The purpose of this study is to provide meaning through semiotic analysis and moral messages that indirectly affect the audience's thoughts and behavior while watching this film. This study uses a semiotic analysis of Roland Barthes' model with a qualitative approach. The results obtained from this study are that the moral messages contained in the hichki film are persistence, independence, never give up, sincerity, cohesiveness, honesty, and affection which are not only given by the main character but also other characters.